Integrating Multimedia Tools in Arabic Teaching within a Multiliteracies Framework / دمج الأدوات المتعددة الوسائط في تعليم اللغة العربية ضمن إطار محو الأمية المتعددة - Fahmy El-Sara; Jonth Mille (IJAS: International Journal of Arabic Studies, 2025)
This study explores the integration of multimedia tools in Arabic language teaching within a multiliteracies framework. The research employs a qualitative descriptive approach to investigate how visual, auditory, interactive, and digital production tools enhance students’ linguistic skills, motivation, and engagement. Data were collected through classroom observations, semi-structured interviews with teachers and students, and analysis of digital learning materials. The findings reveal that multimedia integration improves comprehension, supports differentiated learning, and fosters collaborative and autonomous learning environments. Additionally, the multiliteracies framework provides a comprehensive pedagogical guide for designing learning experiences that align with contemporary technological and cultural contexts. The study highlights the importance of professional development, technological infrastructure, and high-quality digital content to maximize the benefits of multimedia-enhanced Arabic instruction. These findings suggest that multimedia integration is essential for modern Arabic pedagogy and contributes to creating culturally responsive and technologically enriched learning environments